XR-Immersive Labs Improve Student Motivation to Learn Kinesiology - Tunur, Tumay; Hauze, Sean W.; Frazee, James P.; Stuhr, Paul T. (Frontiers in Virtual Reality, 2021)
Kinesiology is an inherently spatial discipline, both physically and visually. The use of extended reality-immersive lab activities may enhance students’ motivation to learn by enabling students to interact with visual content and illustrate and demonstrate kinesiology content and concepts. Using an instrumental case study method, this article assesses the use of extended reality immersion across three semesters of an upper division kinesiology course focused on motor control. This is a unique approach because it blends established physical motor control and biomechanical data collection techniques with emerging virtual reality technology to enhance—rather than replace—the lab experience. The effectiveness is measured via an experimental design to contribute to the small, but growing, body of knowledge on the efficacy of immersive learning.